2021
DOI: 10.3389/fphys.2021.622987
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction in Frontline Health Care Professionals During COVID-19 Pandemic in Brazil

Abstract: Upper respiratory viral infections can decrease the sense of smell either by inflammatory restriction of nasal airflow that carries the odorant molecules or through interference in olfactory sensory neuron function. During the coronavirus disease 2019 (COVID-19) pandemic, triggered by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), worldwide reports of severe smell loss (anosmia/hyposmia) revealed a different type of olfactory dysfunction associated with respiratory virus infection. Since self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Although these dysfunctions are common in the early stages of infection, they are often overlooked by patients as perceived as harmlessness and common, with rates of approximately 3–20% of those who are affected by COVID-19, with a large severity range [ 7 ]. COVID-19 patients present rates of olfactory and gustatory disfunction of 41.0% and 38.2% [ 8 ], respectively, with some studies presenting prevalence as high as 83.9% [ 9 ]. Although complete recovery is common, 5% of the patients report no chemosensory recovery [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these dysfunctions are common in the early stages of infection, they are often overlooked by patients as perceived as harmlessness and common, with rates of approximately 3–20% of those who are affected by COVID-19, with a large severity range [ 7 ]. COVID-19 patients present rates of olfactory and gustatory disfunction of 41.0% and 38.2% [ 8 ], respectively, with some studies presenting prevalence as high as 83.9% [ 9 ]. Although complete recovery is common, 5% of the patients report no chemosensory recovery [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar animal experiments using MERS‐CoV, SARS‐CoV, and SARS‐CoV‐2 support HBC and OSN infection as a precurser to reaching the CNS via olfactory nerves. 55 , 56 , 57 The majority of Covid‐19 patients experience smell or taste disorders 58 , 59 , 60 , 61 ; this neurotoxic effect of SARS‐CoV‐2 might be due to changes in phosphorylation pattern of proteins associated with axons and synapses in olfactory/gustatory neurons or injuries to any of VII, IX, X cranial nerves and the nucleus of solitary tract. 50 , 62 Moreover, the molecular mechanism of virus transportation inside PNS and brain parenchyma neurons is almost identified in the neuronal route.…”
Section: Potentioal Routes Of Direct Cns Invasionsmentioning
confidence: 99%
“…Using the Newcastle-Ottawa scale [51] to assess the risk of bias in each of the included studies, most of the studies were of moderate risk of bias except for 6 studies [34,[149][150][151][152][153] which had high risk of bias, as shown in Figure A1. Most studies utilised hospital instead of community controls, failed to control for age as a variable, failed to blind patients and interviewers to the COVID-19 test result during assessment of GD, and failed to report the non-response rate of their study.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Alizadehsani [142] Altman [143] Beltrán-Corbellini [176] Bénézit [34] Bidkar [139] Boudjema [140] Carignan [177] Chas [144] Chen [149] Cho [178] Dawson [179] Dixon [180] Dreyer [150] Elimian [181] Fistera [145] Ganz-Lord [146] Gibbons [151] Gurrola [182] Izquierdo-Domínguez [183] Jeyashree (1) [141] Jeyashree (2) [141] Karni [152] Kempker [184] La Torre [185] Leal [186] Lee [187] Martin-Sanz [188] Martinez-Fierro [189] Moeller [147] Moolla [190] Nakanishi [191] Pérula de Torres [192] Raberahona [148] Riestra-Ayora [193] Rojas-Lechuga [194] Sayin [195] Sbrana [153] Sonoda [196] Trachootham [197] Trubiano [198] Tudrej [199] Villerabel [200] Yan [201] Zayet (1) [202] Zayet (2) [203] Appendix D Specify the methods ...…”
Section: Conflicts Of Interestmentioning
confidence: 99%